In Vitro Regeneration of Dendrobium sp. of Orchid Using Leaf Tip as Explant - Goswami, K; Yasmin, S; Nasiruddin, KM; Khatun, F; Akte, J (Journal of Environmental Science and Natural Resources, 2016)
Plant growth regulators (PGRs) namely, 2,4-D, NAA and BAP were added into Murashige and Skoog (MS) medium to observe the effect of PGRs on the growth and development of Dendrobium sp. orchid. Leaf tips of Dendrobium sp. were used as explants and inoculated on MS medium supplemented with 2, 4 D (0, 0.5, 2.5, 5, 10 mgL?1) for development of PLBs. The maximum PLBs formation (90%) and the maximum number of PLBs (16.00) were observed in 10 mgL?1 2, 4-D into MS medium after 60 days of culture. Subcultured PLBs were inoculated on MS medium supplemented with different combinations of NAA (0, 0.5, 2.5, 5 mgL?1) and BAP (0, 0.5, 2.5, 5 mgL?1) for shoot regeneration. The maximum number of shoot (11.00), the highest fresh weight (0.6233g) and the highest shoot length (3.613 cm) were observed in 0.5 mgL?1 NAA + 0.5 mgL?1 BAP after 60 days of culture. Even, the maximum number of root (4.00), the maximum root length (1.627cm) and the maximum plantlet regeneration percentage (93.33%) were observed with the combined effect of 0.5 mg NAA and 0.5 mg BAP after 60 days of culture. Finally, regenerated plantlets were transferred into half strength MS medium to obtain plants. J. Environ. Sci. & Natural Resources, 8(2): 75-78 2015